Theory-based behaviour modification of Asian adults with type-2 diabetes mellitus after participating in a novel telemonitoring system: a qualitative research study - Seng Bin Ang; Gerald Choon Huat Koh; Ngiap Chuan Tan; Cia Sin Lee; Pei Pei Gong; Shawn Kuan Liang Goh (BMJ Open)
Objective Telemonitoring (TM) remotely monitors individuals’ health. Awareness of personal clinical data has resulted in improved glycaemic control in adults with type-2 diabetes mellitus (T2DM). However, its effects on their health-seeking behaviour remain unclear. This study aims to explore and understand the effects of a multicomponent TM system on self-efficacy in adults with T2DM.Design A qualitative study using semistructured interviews.Setting A public primary care clinic which is located at an estate in north-eastern Singapore with a population of about 300 000 multiethnic Asian residents.Participants 21 participants who completed 6 months of TM intervention which included immediate feedback on glucose and blood pressure readings, educational videos on exercise and nutrition, and personalised support with TM nurse when clinical parameters met high glucose or blood pressure thresholds.Results The health belief model was used to explain the participants’ behaviour change, including (1) immediate feedback from TM clinical parameters (blood pressure and glucose), raised their awareness of their health status and disease control to motivate behaviour change; (2) notification of higher glucose through TM allowed patients to reflect on their recent food consumption and nudged them to select healthier food options; (3) App teleeducation improved health literacy and supported lifestyle changes; (4) cues for action through personalised engagement with TM nurse and via automated reminders and (5) the TM system enhanced self-efficacy by modifying their multifaceted self-care behaviours.Conclusion TM heightened understanding among adults with T2DM of their potential for health complications and increased awareness of the benefits of proper diabetes management. It also helped lower the barriers to self-management and further enhanced their self-efficacy in self-care. The system and care team provided users with cues for health which was perceived to lead to adapting their lifestyle in order to achieve better health outcomes.Clinical Trials registration number NCT04306770